Evaluation of Sexual Dimorphism of Foramen Magnum: A Morphometric Study - Pinki Kumari; Aman Kumar; Sanjeev Kumar; Saroj Kumar Ranja (Asian Journal of Medical Research, 2019)
Background: Sex determination from skull morphology  is  important  in medico-legal  cases.  The  foramen  magnum  is  an  important structure  of  the  skull  base  and  is  of particular  interest  for forensic experts. Aim: In this study the foramen magnum was analyzed for sex differences using standard osteometric techniques for the North Indian Population. Subjects and Methods: This study included 100 completely ossified dry human skull (M=F) in good condition with a record of sex. The cranial base was visually assessed for foramen magnum shape. Morphometry was determined using vernier caliper and the differences amongst gender were ascertained. Results: Oval shape was the most common followed by round, tetragonal and pentagonal in both sex. The results demonstrated that sexual dimorphism is present in the foramen magnum. APD and TD were higher in male skulls than females. Conclusion: In incomplete skeletons, metric analysis of the foramen magnum may provide a statistically useful indication as to sex of the unknown skull.